Direct and indirect healthcare costs of rheumatoid arthritis patients in Turkey - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2016)
Objective To estimate the annual cost of rheumatoid arthritis (RA) in Turkey by obtaining real-world data directly from patients. Methods In this cross-sectional study, RA patients from the rheumatology outpatient clinics of 10 university hospitals were interviewed with a standardised questionnaire on RA-related healthcare care costs. Results The study included 689 RA patients (565 females) with a mean age of 51.2 +/- 13.2 years and mean disease duration of 9.4 +/- 7.8 years. The mean scores of the Routine Assessment of Patient Index Data 3 and the Health Assessment Questionnaire Disability Index (5.08 +/- 2.34 and 1.08 +/- 0.68, respectively) indicated moderate disease activity and severity for the whole group. One-third of the patients were on biologic agents and 12% had co-morbid conditions. The mean number of annual outpatient visits was 11.7 +/- 9.6 per patient. Of the patients, 15% required hospitalisation and 4% underwent surgery. The mean annual direct cost was 4,954 (median, 1,805), whereas the mean annual indirect cost was 2,802 (median, 608). Pharmacy costs accounted for the highest expenditure (mean, 2,777; median, 791), followed by the RA-related consultations and expenses (mean, 1,600; median, 696). Conclusion RA has a substantial economic burden in Turkey, direct costs being higher than indirect costs. Although both direct and indirect costs are lower in Turkey than in Europe with respect to nominal Euro terms, they are higher from the perspectives of purchasing power parity and gross domestic product. Early diagnosis and treatment of RA may positively affect the national economy considering the positive correlation between health care utilisations and increased cost with disease severity.
Keywords: rheumatoid arthritis; healthcare cost; Turkey; economic burden of disease; QUALITY-OF-LIFE; BURDEN; FRANCE; ACCESS